Renal Morphology in Cats With Diabetes Mellitus. (November 2014) - Zini, E.; Benali, S.; Coppola, L.; Guscetti, F.; Ackermann, M.; Lutz, T. A.; Reusch, C. E.; Aresu, L.
In humans, diabetes mellitus (DM) is an important cause of renal damage, with glomerular lesions being predominant. In cats, although diabetes is a common endocrinopathy, it is yet unknown whether it leads to renal damage. The aim of the study was to compare renal histologic features and parameters of renal function in diabetic cats against a control population matched for age, gender, breed, and body weight. Thirty-two diabetic and 20 control cats were included. Kidney sections from paraffin-embedded kidney samples were stained and examined with optical microscopy to identify glomerular, tubulointerstitial, and vascular lesions and to assess their frequency and severity. Serum creatinine and urea concentrations were also compared. Glomerular lesions were observed in 29 cats overall, with mesangial matrix increase being more common (19 cats). Tubulointerstitial lesions were observed in 42 cats, including lymphocytic infiltration (29), fibrosis (22), or tubular necrosis (21). Vascular lesions were observed in 5 cases. The frequency and severity of histologic lesions did not differ between diabetic and control cats; however, among diabetics, those that survived longer after diagnosis had more glomerular and vascular lesions. Serum creatinine and urea concentrations were similar between groups; in diabetic cats median creatinine was 109 μmol/l (range, 51–1200) and urea was 12 mmol/l (range, 4–63), and in controls creatinine was 126 μmol/l (range, 50–875) and urea 11 mmol/l (range, 3–80). The results suggest that DM in cats does not lead to microscopically detectable kidney lesions or clinically relevant renal dysfunction. The authors hypothesize that the short life expectancy of diabetic cats may be the main reason for the difference from human diabetics.